Jamie's America - Oliver, Jamie, 1973- (Michael Joseph, 2009)
Jamie's America sees Jamie on a personal journey. On the surface of things, given its reputation for fast food and obesity, America is perhaps an unusual place to go looking for inspiration and new recipe ideas. But as ever Jamie digs beneath the surface and discovers what real American food is all about. Embarking on a culinary road trip across the States, Jamie visited six very different places, embracing a wealth of new ideas, people and ingredients. His trip takes him to New York, Louisiana, Arizona, Los Angeles, Georgia and Wyoming. But even in cities such as LA and New York, he has avoided the obvious foodie places. Instead Jamie has looked beyond the American stereotypes to discover the real food, the accessible and affordable classics that make this country tick. This journey turned into the most inspiring food and travel adventure of his life.